Decision-making in a corporate boardroom: Inside the black box - Martyn, Karen (Massey University, 2006)
The lack of empirical studies on board process represents a serious knowledge gap in the governance literature. To date there has been little research on how boards actually make decisions, the factors that contribute to effective board decision-making, and what tools and techniques may be used to improve board decision-making. Effective board processes are identified as leading to effective board outputs, and subsequently more effective organisational outcomes. This study explored the internal factors under the control of the board (or those selecting board members) that contribute to effective board decision-making processes. The perspective of small group decision-making research was applied to explore board decision-making processes. The three aims of the study were to investigate those factors that directors thought contributed to their board's successful and unsuccessful decision-making, to observe how a board actually makes decisions; and to determine whether training and usage of a normative decision-making methodology (including the use of a reminder role) might improve that board's decision-making process. Data collection included direct, in situ, observation of a board; semi-structured interviews with all board directors, the CEO and four executive team members; three surveys; and emotional intelligence testing (MSCEIT). The board was found to use normative decision-making procedures. These decision making procedures appeared to contribute to better decision-making processes and consequently better decision-making outputs. The task intent of acting in the best interest of the company and the relationship intent of trust were found to permeate the board inputs and processes examined during this research. Other input and process variables observed to influence board decision-making were classified as being task (structure, process, communication) and/or relational (relationships, director attributes and emotions) factors. Task factors included rational decision-making procedures; clarity of goals and roles; use of external advisors as critical evaluators; quantity and quality of information; consensus decision-making; post-decision evaluation and learning. Relational factors included homogeneity of directors through careful selection; socialising with management; board norms of a safe environment, supporting the doubtful director and the obligation to share contrary views; adequate business knowledge; emotional intelligence; and commitment. The results of emotional intelligence testing revealed levels sufficient to assist in positive board dynamics. The study results support the application of small group decision making research to aid in board process research, and further empirical exploration of board inputs using psychometric measures.
Keywords: Decision-making; Boards of directors; Corporate governance; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management